A Systematic Study of the Limits of Life in Mixed Ion Solutions: Physicochemical Parameters Do Not Predict Habitability - Stevens, Adam H.; Cockell, Charles S. (Frontiers in Microbiology, 2020)
This study investigated what defines the limits of life in mixed ion solutions. Better understanding these limits should allow us to better predict the habitability of extreme environments on the Earth and extraterrestrial environments. We systematically examined the response Bacillus subtilis, a well characterized non-halophile model organism, to a range of solutions made from single and mixed salts up to their solubility limits and measured at what concentration growth was arrested, specifically exploring Na, Mg and Ca cations and Cl, SO4 and ClO4 anions. We measured the physicochemical properties of the solutions to identify which properties correlated with the limits of growth. Individual salts imposed a growth limit specific to the combination of cation and anion, although we generally observe that chloride salts allow growth at lower water activity than sulfate salts, with perchlorate restricting growth even at the highest measured water activity. Growth was limited at a wide range of ionic strength, with no apparently correlation. Despite the theoretically counteracting disordering effects (chaotropic) of perchlorates and ordering effects (kosmotropic) effects of sulfates, when these salts were combined they instead additively narrowed the window for growth in both the Na and Mg cation systems, in the same manner as the combined effects of two chaotropic Ca salts. Our results imply that away from hard limits that might be imposed by physicochemical properties such as water activity, ionic strength or chaotropicity in highly concentrated brines, these properties do not set the limits of life. Instead these limits are highly specific to the salts and organisms in question. This specificity means that the habitability of extreme environments cannot be predicted, even with accurate measurements of the physicochemical conditions present.